Incidence and predictors of HIV, chlamydia and gonorrhoea among men who have sex with men attending a peer-based clinic - Selvey, Linda; Slimings, C.; Adams, E.; Manuel, J. (C S I R O Publishing, 2018)
© 2018 CSIRO. Introduction: Despite a range of interventions, annual numbers of new diagnoses of HIV infection among men who have sex with men (MSM) in Australia have not declined in recent years. Peer-based sexual health clinics targeting MSM, such as the M Clinic in Perth (WA, Australia), have been put in place to provide safe sex counselling and to increase testing rates among MSM and who are at high risk of HIV infection. The aim of this study was to assess the incidence of HIV, chlamydia and gonorrhoea among men attending the M Clinic. Methods: This was a historical cohort study of repeated M Clinic clients from January 2011 to June 2015 inclusive. Testing and risk factor data from M Clinic client software were used to estimate the incidence of HIV, chlamydia and gonorrhoea and associated factors. Results: The incidence of HIV, chlamydia and gonorrhoea was 1.87, 13.58 and 6.48 per 100 person-years respectively. Older men had a higher incidence of HIV infection but a lower incidence of chlamydia and gonorrhoea than younger men. Conclusions: The HIV incidence was higher than found in similar studies in other Australian sexual health clinics, but the incidence of chlamydia and gonorrhoea was similar. The high HIV incidence among clients of the M Clinic points to the importance of making pre-exposure HIV prophylaxis available to clients of the M Clinic and similar services.